PENINGKATAN KUALITAS PROD UK KERAJINAN BERBAHAN BAKU SERAT ALAMI MELALUI INOVASI DESAIN - Suharto, Suharto (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2005)
There  was  guiding  program  on handicraft  industry  for  craftsmen   at Penguin,  Kulonprogo   Regency.   The  goal  of  the  elucidation   of  handicraft development   was  to  increase   the  quality  of  handicraft   design   in  order  to make  it more  competitive   in the market.  The guiding  program  aimed  to de velop the craftsmen's   knowledge   and skill to be able to create  their  own de sign. This would  make  them  not rely only on customers  who had the design. The guiding  program  also  gave  insight of how to manage  the handicraft   in dustry that covered  human  resources  management,  production,   product  mar keting, and the other process  in the industry.The  guiding  program   used  lecturing  method  given  to the  craftsmenPengasih pendopo   (the audience  hall of the sub-district)  which  was attended by the sub-district   officials  and  19 craftsmen  from  four types  of the handi craft industry:  rope-craft,  coconut-fiber-craft,   bamboo-craft,   and wood  carv ing. After  lecturing,  tutors  team  gave design models  of handicraft  to add de sign varieties  in order  to train  the craftsmen  in creativity.  This  plain  training would be evaluated  and  criticized  by the tutors to make  it a continued   pro cess.The product  of handicrafts   involved:  crafts  made  of coconut-fiber    such  asdoormat  and  brooms;   crafts  made  of rope  used  agel,  rami,  mendong,   and enceng  gondok   material:   bags  and  cases;  crafts  made  of  bamboo   such  as furniture  and bird- cages;  and wood carving. The entire product  was resulted from mariual work with plain design. To product handicrafts  is a side job  for the men whose  main jobs  are farmers.  They use their free time while  waiting harvest for making  the handicrafts.Key word: the development   of handicrafts   design